OBSERVATIONS ON THE INDIAN SHORT-FJNNED EEL ANGUILLA BICOLOR BICOLOR McCLELLAND CAUGHT FOR THE FIRST TIME AT SEA DURING SPAWNING MIGRATION - Dorairaj, K; Nandakumar, G (Indian Journal of Fisheries, 2011)
One migrant Indian short-finned female silver-eel, Anguilla bicolor bicolorMcClelland, measuring 866 mm in total length and 1150 g in weight, caught alivefor the first time from the inshore area off Karwar in July 1980, is recorded.Salient morphological, morphometric and gonadal characteristics of the migranteel, compared with those of non-migrant and partially spawned female eels, confirmedthat the eel was in a maturing stage and was on its way to oceanic spawningground.